Brain machine interface: Analysis of segmented EEG signal classification using short-time PCA and recurrent neural networks - Hema, Chengalvarayan Radhakrishnamurthy; Paulraj, Murugesa Pandiyan, Assoc. Prof.; Nagarajan, Ramachandran, Prof. Dr.; Sazali, Yaacob, Prof. Dr.; Abdul Hamid, Adom, Prof. Madya (University of Basrah, 2011)
Link to publisher's homepage at http://www.uobasrah.edu.iq/